Math tricks the surprising wonders of shapes and numbers - Posamentier, Alfred S. (Prometheus, 2021)
"In his latest book, mathematician Alfred S. Posamentier provides easily understandable, easily presentable and easily replicated tricks that one can do with mathematics"--